Harnessing oncolytic viruses to overcome immunosuppression in breast cancer: from mechanisms to clinical translation - Xianshu, Kong; Zhonghua, Liu; Junyu, Dong; Qing, Peng; Li, Zhang; Feiyue, Zhang; Xuqing, Su (Frontiers in Immunology, 2025)
Oncolytic viruses (OVs) possess dual advantages in cancer immunotherapy: they selectively replicate within and lyse tumor cells while simultaneously releasing tumor-associated antigens to recruit and activate immune cells within the local tumor microenvironment (TME), thereby inducing robust and sustained antitumor immunity. Furthermore, these viruses can serve as tumor-targeting vectors for immunomodulation and synergize with other immunotherapeutic approaches. As such, oncolytic virotherapy holds significant potential to overcome the low response rates of breast cancer to existing immunotherapies and expand the therapeutic arsenal. This review systematically elucidates the application and mechanisms of this emerging immunotherapy in addressing the challenges of conventional breast cancer treatments. It also discusses engineering strategies to enhance antitumor immunity, highlights recent preclinical and clinical studies on rational combinations of OVs with other therapies, and outlines current challenges and future prospects.